Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Purification by silica gel chromatography using dialysis tubing and characterization of sophorolipids produced from Candida bombicola grown on glucose and arachidonic acid - Shah, Sachin; Prabhune, Asmita (Biotechnology Letters, 2007)
The yeast Candida bombicola (ATCC 22214) grown on primary carbon source glucose (100 g l(-1)) and secondary carbon, arachidonic acid (2 g l(-1)) produced mixture of sophorolipids up to 1.44 g l(-1). The crude product was a heterogeneous mixture of sophorolipids, which are glycolipids of sophorose linked to the fatty acid through glycosidic bond between omega and omega-1 carbon of arachidonic acid. The derived sophorolipids were isolated by silica gel chromatography using dialysis tubing. The purified sophorolipids were characterized by ESI-MS and FT-IR. Acid hydrolysis of the resolved sophorolipids were characterized by ESI-MS for the presence of 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE) and 19-hydroxy-5Z,8Z,11Z,14Z-eico-satetraenoic acid (19-HETE), compounds of pronounced pharmaceutical importance.
Keywords: 19-HETE; 20-HETE; arachidonic acid; electrospray soft ionization mass spectroscopy; silica gel chromatography; Sophorolipid

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase

Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis

Pulsed laser-driven molecular self-assembly of cephalexin: aggregation-induced fluorescence and its utility as a mercury ion sensor - Singh, Pradeep Kumar; Prabhune, Asmita; Ogale, Satishchandra (Photochemistry and Photobiology, 2015)
A fluorescent self-assembly of cephalexin is obtained by pulsed laser irradiation process. An intense fluorescence emission is found in the self-assembled form due to occurrence of a typical aggregation-induced emission in cephalexin molecules. It is observed that fluorescence quenching of the self-assembled fluorescent nanostructures occurs in the presence of extremely low Hg++ ions concentrations (10(-7) M) as compared to other heavy metal ions e.g. Ferrous (Fe++), Manganese (Mn++), Magnesium (Mg++), Cobalt (Co++), Nickel (Ni++) and Zinc (Zn++) at the same concentrations.

Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid